Cardiovascular actions of mineralocorticoid receptor antagonists in patients with chronic kidney disease: A systematic review and meta-analysis of randomized trials. (September 2015) - Ng, Khai P; Arnold, Julia; Sharif, Adnan; Gill, Paramjit; Townend, Jonathan N; Ferro, Charles J
Introduction: The safety and actions of mineralocorticoid receptor antagonists on surrogate markers of cardiovascular disease as well as major patient level cardiovascular end-points in patients with chronic kidney disease are unclear. Methods: MEDLINE, EMBASE, Trip Database, Cochrane Central Register of Controlled Trials, Cochrane Renal Group specialized register, Current Controlled Trials and clinicaltrials.gov were searched for relevant trials. Results: Twenty-nine trials (1581 patients) were included. Overall, mineralocorticoid receptor antagonists lowered both systolic and diastolic blood pressure (–5.24, 95% confidence interval (CI) –8.65, −1.82 mmHg; p =0.003 and −1.96, 95% CI −3.22, –0.69 mmHg; p =0.002 respectively). There were insufficient data to perform a meta-analysis of other cardiovascular effects. However, a systematic review of the studies included suggested a consistent improvement in surrogate markers of cardiovascular disease. Overall, the use of mineralocorticoid receptor antagonists was associated with an increased serum potassium (0.23, 95% CI 0.13, 0.33 mmol/l; p <0.0001) and higher risk ratio (1.76, 95% CI 1.20, 2.57; p =0.001) of hyperkalemia. Data on long-term cardiovascular outcomes and mortality were not available in any of the trials. Conclusions: The long-term effects of mineralocorticoid receptor antagonists on cardiovascular events, mortality and safety need to be established.